FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG BERAS DALAM MENGHADAPI FLUKTUASI HARGA DI KOTA MANADO - Ernia . Sondakh; Rine . Kaunang; Paulus Adrian Pangemanan (AGRI-SOSIOEKONOMI, 2016)
The purpose of this study is to analyse the factors that influence rice traders income to price increases in Pasar Bersehati Calaca and Pasar Pinasungkulan Karombasan Manado. To answer this purpose, analysis of multiple regressions is used. The study is conducted from December 2015 to January 2016 by using secondary data of Badan Pusat Statistik Sulawesi Utara, namely percentage price change from January 2015 until Desember 2015, and primary data taken from rice traders by using questionnaire. Result show that capital, price, stock, and output simultaneously have significant influence to income of rice traders. Partially, capital and output have positive influence to income of rice traders, whereas price and stock have negative influence to income of rice traders. ls & rr.